Regulating the international activities of Russian higher education institutions - V. V. Bondarenko; N. A. Nazarova; K. S. Taisheva; D. P. Penzina (Вестник университета)
One of the key conditions for increasing of Russian education competitiveness in the international market is the active involvement of universities in various international cooperation forms. For this purpose, an analysis of international, federal, local normative legal acts regulating the international activities of Russian higher education institutions was carried out. The international aspect was considered using a comparative legal analysis of agreements between Russia and other countries. The article presents the results of the analysis of the principles of international agreements regulating the educational process in Russian universities. According to the research, a model, regulating the international activities of Russia’s universities, was analysed. The study of regulatory legal acts in Russia’s higher education led to the conclusion about the legislation elaboration level, to outline the prospects for development and the possibility of expanding the domestic universities international activities.